Ultrahigh molecular weight polyethylene-reduced graphene oxide composite scaling up to produce wear resistant plates - Amurin, Leice Gonçalves; Oliveira, Poliane Neves De; Pereira, Ana Flávia Tavares S.; Ribeiro, Nirvana Cecília; Rezende, Daniel Bastos De; Silva, Glaura Goulart (Frontiers in Carbon, 2023)
Maintaining the properties of nanocomposites obtained at the laboratory scale when evolving to pilot and industrial scales is a great challenge. In this work, the route for a 3000-fold increase in scale between the laboratory and production in an industrial environment was conducted in two stages -Pilot 1 and Pilot 2 -to obtain polymeric nanocomposite plates for pilot testing. The nanocomposite was based on ultrahigh molecular weight polyethylene (UHMWPE) and reduced graphene oxide (rGO), and several different operations were optimized for complete scale-up, i.e., i) production of reduced graphite oxide (rGrO); ii) exfoliation of rGrO; iii) milling of rGO with UHMWPE in a ball mill to produce masterbatch; and iv) RAM extrusion to produce the plates. All these steps were accompanied by characterizations that show the quality of the nanomaterial, masterbatch and nanocomposite plates. The gains in nanocomposite properties with 0.25 wt% rGO with respect to UHMWPE were ~ 45% in elastic modulus, ~ 50% in hardness, ~ 25% in impact strength and 15% in abrasion wear (two-body test). The nanocomposite surfaces after wear tests are more hydrophobic than UHWWPE. The Pilot 1 results were generally superior to the Pilot 2 results, probably due to the very different thicknesses of the plates, i.e., 10 mm in Pilot 1 and 40 mm in Pilot 2. The improvement in different properties confirms the multifunctionality of the nanocomposite UHMWPE/rGO now produced on a pilot scale.